Studies on Aging Behavior and Degradation Mechanism of Raw EPDM Rubber Under γ-Ray Irradiation - Xin-yi, Du; Sheng-nan, Jiang; Qing, Zhao; Meng-yuan, Zhu; Hong-zhen, Wang; Cun-guo, Wang; Ai-hua, He; Xin, Ye; Bo, Zhao (Journal of Composites and Biodegradable Polymers, 2023)
The aging behavior and mechanism of EPDM rubber were investigated by conducting different doses of γ-rays irradiation in raw EPDM rubber. A series of characterization methods such as Mooney viscosity, molecular weight and its distribution, rubber processing analysis, infrared spectroscopy analysis et al. were carried out. Structure and modifications of the raw EPDM rubber were tested under different irradiation doses. The results showed that the Mooney viscosity and molecular weight of EPDM rubber showed a significant decrease with increasing irradiation dose. The gel content and glass transition temperature increased gradually. As strain rose, the energy storage modulus diminished. The loss factor decreased at first and then increased with increasing strain during irradiation aging.